Life after Johnnie Cochran : why I left the sweetest-talking, most successful Black lawyer in L.A. - Cochran Berry, Barbara (Basic Books, 1995)
Life After Johnnie Cochran is the story of the woman who put up with philandering, physical abuse, mind games, put-downs, and even a long-term white mistress before she grabbed her two young daughters and her dignity and walked away from her eighteen-year marriage to L.A.'s most successful black lawyer. The future captain of the dream team, according to Cochran Berry, was a "nightmare to live with," able to come up with a dozen good answers to the simplest of questions, like: "Where did you spend the night?" The author explains why she chose to ignore the received wisdom of those days among black middle-class women that said, "No matter what, you don't leave a man who can pay the bills."